Del alimento al guiso : fiesta y alimentación entre los yoremes de Sinaloa, México - Hugo E. López Aceves (Les Cahiers ALHIM)
Within Mexico´s Native Northern Sinaloan Yoremes (or mayos), ceremonial activities allow us a glimpse into the symbolic value of food as it relates to ritual life and religious practice. In addition, it illuminates a conceptualization of ceremonial sustenance and the particular ways it is obtained and processed. Under their ramadas, ceremonial food is represented vis-a vis its nexus with domestic areas where it is prepared. Nonetheless, a distinction between domestic and ritual landscapes and temporal cycles does not signify binominal oppositions between man-nature or that of pueblo-wilderness, but rather suggests dynamic and complementary relationships. This article argues that the processing of ceremonial food in the Mayo Indian domestic areas expresses particular values, reciprocity and the creation of social alliances, in addition to its representing cultural resistance.